Early radiological and functional outcomes for a cementless press-fit design modular femoral stem revision system. Issue 1 (January 2019) - Hancock, Douglas S; Sharplin, Paul K; Larsen, Peter D; Phillips, Fredrick TS
Aim: To assess early radiological and functional outcomes of revision hip surgery with a cementless press-fit design femoral stem. Patients and methods: A retrospective review of 48 consecutive revision total hip replacements using the RECLAIM revision hip system, between October 2012 and August 2015. Radiographic assessment was undertaken with serial anteroposterior (AP) X-rays of the pelvis. Risk factors for subsidence were evaluated. Prospective clinical follow up was performed on 21 patients to assess functional outcomes. Results: Mean stem subsidence was 1.1 mm (95% confidence interval[CI]: 0.63–1.57). Median follow up of 12 months. An inverse relationship was observed between level of subsidence and femoral stem diameter r = −0.45, p = 0.001. Subsidence at the time of follow-up assessment was correlated with initial subsidence (correlation coefficient rho 0.69, p = 0.001). The mean Merle d'Aubigne score at the latest follow up was 14.2 (range 8–17). The mean OHS was 34.1 (range 15–48). Conclusion: Early radiological and functional outcomes for the RECLAIM revision system showed very low levels of subsidence and good functional outcomes. There was an association with smaller diameter femoral stems and greater levels of subsidence.